ANALISIS TEKNIK PENERJEMAHAN SUBTITLE SERIAL DRAMA GO AHEAD EPISODE 1 - Sianturi, Shelly Febriani; Adha, Tengku Kasa Rullah (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2022)
Translation is a skill used to translate the source language into the target language by applying several translation techniques to produce translation products that are readable, acceptable and accurate. One of the translation products that is closest to the public is subtitles. This study aims to analyze how the translation techniques applied to the drama series Go Ahead Episode 1. The research method used to analyze the research data is descriptive qualitative. The results of this study indicate that the translator of the drama series Go Ahead Episode 1 uses 16 translation techniques, namely 20% (12 data) compensation techniques, 15% (9 data) literal translation techniques, 11.68% (7 data) amplification techniques and transposition techniques, 10% (6 data) reduction technique, 8.31% (5 data) adaptation technique, 5% (3 data) linguistic compression technique, 3.32% (2 data) description technique and 1.67% (1 data) respectively borrowing technique, kalke technique, common equivalence technique, generalization technique, modulation technique, substitution technique, and variation technique.Key word : translation, translation technique, subtitle.